SYPHILIS IN EMERGENCY DEPARTMENT: CONDITION OF THE ISSUE AND UNRESOLVED PROBLEMS - I. A. Bagretsova; A. V. Sukharev; I. M. Barsukova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2019)
Introduction. The development of the system of emergency medical care in emergency department inevitably brings up issues of its availability and quality. Moreover, if the leading pathological syndrome resulting in the hospitalization and threating to the patient’s life deserves priority attention, so the accompanying pathology often remains in the shadow. Thus, venereal diseases, in particular, syphilis is epidemiologically dangerous disease as for the patients having this illness and for the patients surrounding them and the medical personnel carrying out the medical process. The objective of the study was to assess the current state of the problem of medical care for patients with venereal pathology in an emergency department.Material and methods. The material for the study was the data of medical records of patients in multispecialised emergency department of St. Petersburg for 4 years: 1088 – with positive serological reaction and 4500 – without dermatovenereal pathology (DVP).Results. By the results of the research, the diagnosis of syphilis was based only on the enzyme immunoassay test for syphilis and the diagnosis of syphilis remained unspecified; the efforts to prevent the spread of syphilis in emergency department were insufficient, did not allow carrying out appropriate preventive, therapeutic and diagnostic measures.Conclusion. Development of new models and principles of the organization of the diagnostic and treatment process, including the introduction of methods of express diagnosis in emergency department is required.